2006
DOI: 10.1159/000095629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Statin Therapy on Clinical Outcomes in Chronic Heart Failure Patients According to Beta-Blocker Use: Results of CIBIS II

Abstract: Background: HMG-CoA reductase inhibitors (statins) are widely prescribed in patients with established systolic chronic heart failure (CHF). However, there is considerable controversy regarding their benefit in this setting. We therefore conducted a post-hoc analysis of outcomes according to statin use within the Second Cardiac Insufficiency Bisoprolol Study of the beta-blocker, bisoprolol, in NYHA classes III–IV systolic CHF patients (left ventricular ejection fraction <35%), eceiving background ACE inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 47 publications
0
7
0
2
Order By: Relevance
“…Reduction in sympathetic activity has been shown to prevent cardiac decompensation in HF patients (53,55,56). In a recent analysis of the Second Cardiac Insufficiency Bisoprolol Study (CIBIS‐II) statins and beta‐blockers were found to have a favourable therapeutic benefit in mortality in HF patients than with either agent used alone (57). Elevated cholesterol levels have been shown to correlate with elevated expression of angiotensin type I receptors which increase the vasoconstrictor impact of angiotensin II on the vasculature (58).…”
Section: Pleiotropic Effects Of Statins: Proposed Mechanisms Of Benefmentioning
confidence: 99%
“…Reduction in sympathetic activity has been shown to prevent cardiac decompensation in HF patients (53,55,56). In a recent analysis of the Second Cardiac Insufficiency Bisoprolol Study (CIBIS‐II) statins and beta‐blockers were found to have a favourable therapeutic benefit in mortality in HF patients than with either agent used alone (57). Elevated cholesterol levels have been shown to correlate with elevated expression of angiotensin type I receptors which increase the vasoconstrictor impact of angiotensin II on the vasculature (58).…”
Section: Pleiotropic Effects Of Statins: Proposed Mechanisms Of Benefmentioning
confidence: 99%
“…Previous studies showed that combination therapy with a beta-blocker and a statin was beneficial in lowering short-term MACEs in patients with coronary arterial disease [ 10 12 , 16 , 17 ]. Combination therapy application at an early stage was suggested to be correlated with reduced mortality and morbidity in patients with MI complicated with heart failure [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies reported beneficial effects of statin in patients with HF, such findings were mostly obtained from observational or retrospective studies. 227) 242) 243) 244) 245) The two large randomized trials CORONA and GISSI-HF, which evaluated the effect of statin treatment in patients with chronic HF, did not demonstrate any improvement in long term outcome. 246) 247) Moreover, there are several reports describing increased mortality in patients with HF and low cholesterol levels.…”
Section: Pharmacological Treatmentmentioning
confidence: 98%